The Impact of Intensifier as Women’s Persuasion Strategy in Politics Vice-Presidential Debate - Britney Caren Joseph; Widyastuti Widyastuti (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2023)
This study aims to analyze the impact of intensifier as a persuasive language strategy in politics used by Kamala Harris as a female politician in the 2020 vice-presidential debate. The study attaches to the qualitative research method focusing to construe in-depth analysis. Two primary sources are used in data gathering: vice-presidential debate transcription from rev.com and the vice-presidential debate video from NBCNews on YouTube. The methodological approach is the qualitative research method. The theoretical framework used as the main theory of this research is Quirk et. al‘s (1992) intensifier theory and Lakoff's (1975) women’s language features. The result found that there are 95 intensifiers. First, emphasizers (58%) with attitudinal and style disjuncts (46%) and 12%. Second, amplifiers (25%) with maximizers (18%) and boosters (7%). Lastly, downtoners (16%) with compromiser (1%), diminisher (1%), minimizer (7%), and approximator (6%). The most prevalent sort of intensifier used by Kamala and Hillary was the emphasizer attitudinal disjunct, e.g.